2021
DOI: 10.22225/ah.3.2.2021.230-234
|View full text |Cite
|
Sign up to set email alerts
|

Perlindungan Konsumen Terhadap Tindakan Pemadaman Listrik yang dilakukan Secara Sepihak Oleh PT. PLN (Persero) UP3 Bali Selatan

Abstract: Indonesia merupakan negara yang terdiri dari beberapa pulau dan setiap wilayah yang ada memerlukan tenaga listrik sebagai kebutuhan sehari – hari maupun kebutuhan jangka panjang, keadaan yang ada saat ini banyak masyarakat mengeluh terhadap pelayanan yang diberikan pihak PLN yaitu pemadaman listrik tanpa pemberitahuan terlebih dahulu. Banyaknya keluhan masyarakat berkaitan dengan pemadaman listrik membuat pihak PLN kelimpungan dalam membenahi struktur organisasi terutama di sektor koordinasi antar pekerja. Pem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Consideringly, in a country with the fourth-largest population in the world with a significant increase in population every year, it is predicted that the household sector will continue increasing electricity demand. Power outages that often occur in several areas in Indonesia force some parties to use their generators to maintain the electrical energy supply for households, offices, and industries ( Kusuma et al, 2021 ; Simanjuntak & Louhenapessy, 2021 ). It is found that the length of the period of doing activities in the homes and the quality of indoor thermal are the main factors that affect electricity consumption ( Gao & Novianto, 2018 ; Tran et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Consideringly, in a country with the fourth-largest population in the world with a significant increase in population every year, it is predicted that the household sector will continue increasing electricity demand. Power outages that often occur in several areas in Indonesia force some parties to use their generators to maintain the electrical energy supply for households, offices, and industries ( Kusuma et al, 2021 ; Simanjuntak & Louhenapessy, 2021 ). It is found that the length of the period of doing activities in the homes and the quality of indoor thermal are the main factors that affect electricity consumption ( Gao & Novianto, 2018 ; Tran et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%